Is vitamin D deficiency contributing to high predisposition to non-communicable diseases in Indians? A review article - Sarkar, Amrita; Roy, Debjit (International Journal Of Community Medicine And Public Health, 2017)
Vitamin D deficiency is highly prevalent in Indians. The role of vitamin D in infectious diseases is a well-known fact. However, more recently, several studies have linked vitamin D deficiency with various non-communicable diseases like hypertension, cardiovascular diseases, diabetes, cancer and psychiatric illnesses amongst others. Indians are known to be prone to developing non-communicable diseases so a co-existing vitamin D deficiency will lead to a synergistic effect towards developing the same. Since vitamin D deficiency is completely preventable, opportunistic screening of people, screening the vulnerable population like the pregnant women and the elderly, patients with hepatic or renal failure, patients on retroviral or immunosuppressant therapy can be useful. Health education and promotion activities should be done to bring awareness in the community. This might as well reduce the growing burden of non-communicable diseases in India.